Business Idea for Starbucks: Organic Yerba Mate Beverages - Basak, Sourav; P.V, Ranjith; A. Prakash, Preethi; Albesis, Ghezlan; Quttainah, Majdi Anwar; Shukla, Sonia; Pandey, Rudresh (AIBPM Publisher, 2020)
The report here is basically a research-based business idea for Starbucks Coffee Company that operates all over the world. The idea is line with the market dynamics and the needs of the target market i.e. the masses across the world. The idea is that Starbucks should start a separate line of coffee shops in various parts of the word that will serve Yerba Mate herbal coffee, tea and Beverages. This is a famous coffee and tea in South Africa that has extensive health benefits and falls in the domain of third wave of coffee for the specialty coffee lovers. This business idea will be implemented by Starbucks as a specific niche in the coffee or restaurant industry. Now since the population of world is facing high rates of obesity, and with increasing quality consciousness and love for specialty coffee, this business idea presents great opportunity for the company. The idea is based on research using market analysis and tools like PEST analysis.